Similar and distinctive features of the lexical-phraseological fields ‘anxiety’ in the Russian, Belarusian, English and German languages - Kornakova, Victoria I. (Journal of the Belarusian State University. Philology, 2023)
The paper considers issues of the interrelationship of language, culture and thinking, the similarities and differences of national languages nominative funds, factors that determine cross-language lexical and phraseological similarities and differences. The classification by M. S. Gutovskaya of nominative units belonging to different languages on the basis of cross-language similarities and differences taking into account linguistic, cultural and cognitive factors is applied. The proportion of lexemes and phrasemes in the categories of similar and distinctive is revealed in both all four languages, and in groups of Slavic (Russian and Belarusian) and Germanic (English and German) languages separately. There is a prevalence of differences in the naming of anxiety both in four languages and in the Germanic languages separately, the prevalence of similarities in the Slavic languages. Differences between lexical and phraseological parts are interpreted in terms of linguistic, cultural and cognitive factors. The leading role of the cognitive factor in the formation of cross-language similarities and differences in phraseology and cross-language similarities in lexics is determined, as well as the decisive role of the linguistic factor in the formation of lexical differences discovered by comparing four languages. The patterns revealed in the intra-group analysis (Slavic languages vs Germanic languages) are explained: the prevalence of cognitively determined phraseological similarities compared to differences of the same type in Slavic languages, a larger percentage of lexical similarities stimulated by linguistic reasons in Slavic languages compared to Germanic.